Syn‐Drift Plate Tectonics - Erkan Gün; Russell N. Pysklywec; Gültekin Topuz; Oğuz H. Göğüş; Philip J. Heron (Geophysical Research Letters)
Abstract The paradigm of plate tectonics holds that ocean plates are rigid during drift and only experience tectonic deformation at subduction zones, but new findings from the Pacific challenge this idea. Geological and geophysical evidence from the Ontong Java, Shatsky, Hess, and Manihiki oceanic plateaux indicates that extensional deformation during plate drift is a widespread phenomenon across the Pacific plate. These anomalously thick oceanic plateaux are weaker regions of the ocean lithosphere and more prone to tectonic deformation. Numerical geodynamic models demonstrate that a slab pull force from distant subduction plate boundaries can be effectively transmitted to oceanic plateaux through strong ocean lithosphere and cause substantial extension during plate drift. Our findings reveal that a wide expanse of the Pacific has experienced syn‐drift plate tectonics linked to pull from the western Pacific subduction factory.